The influence of individual factors, transfer climate, and training design on training transfer: the mediating role of motivation to transfer / Sharrifah Ali - Ali, Sharrifah (Institute of Graduate Studies, UiTM, 2016)
Both organizations and employees in recent decades have increasingly focused their attention on lifelong and continuous training. This phenomenon is strongly related to the extension of working life which leads to socio-economical effects and new challenges for employees specifically in knowledge, skills, and attitudes (KSA). In order to improve employees’ KSA, and to create an intellectual capital that perfectly fits the organization’s culture, most organizations provide learning opportunities (training) to their employees. Although training is not the only way for employees’ learning to occur, the investment made in training requires an analysis of certain evidence to determine if, indeed, training pays off in organizational effectiveness. Specifically, training alone will do little to increase employees or organizational performance unless what is learned as a result of training is transferred into on-the-job behaviour. Review of related international literatures revealed the importance of training transfer, nevertheless, there is lack of empirical evidence to support this in the Malaysian context and this study contributes a deeper understanding of some of the critical aspects of training transfer…